Associations between family religious practices, internalizing/externalizing behaviors, and body mass index in obese youth. (April 2015) - Limbers, Christine A; Young, Danielle; Bryant, William; Stephen, Matthew
The objective of the present study was to assess the associations among family religious practices, internalizing/externalizing behaviors, and body mass index in a sample of severely obese youth referred to an outpatient pediatric endocrinology clinic. The sample consisted of 43 obese youth (body mass index > 95th percentile) aged 6–16 years (mean age = 12.67 years). Approximately 93% of families endorsed their religious faith as Christian or Catholic. Parents of youth were administered a demographic questionnaire, religiosity questionnaire, and the Child Behavior Checklist. Three multiple linear regression models were examined with body mass index percentile, Child Behavior Checklist Internalizing Scale, and Child Behavior Checklist Externalizing Scale as outcome variables. A parent endorsing greater importance of religious faith in shaping family life was associated with lower child body mass index percentile ( p  < 0.05) in the present sample. Greater family attendance at religious services was associated with higher child body mass index percentile ( p  < 0.05). Our data suggest that church-based interventions may be one viable option for the delivery of lifestyle interventions in families of youth with severe obesity.